2008
DOI: 10.1016/j.juro.2008.03.182
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression After Vaginal Distention of Different Durations in Virgin Sprague-Dawley Rats

Abstract: These data support a relationship between vaginal distention duration and the subsequent expression of monocyte chemotactic protein-3 and 1 of its associated receptors, CCR1, in the urethra immediately following vaginal distention. The increase in hypoxia-inducible factor1alpha expression in the urethra with prolonged vaginal distention suggests a limited role of tissue ischemia in the immediate response of pelvic organs to vaginal distention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 20 publications
5
48
0
Order By: Relevance
“…This is consistent with previous work showing marked edema after 4 h of VD associated with thinning of the UVS and interstitial swelling between striated muscle fibers (28). In addition, we previously showed that the urethra is the only organ demon- strating a significant increase in hypoxia-inducible factor-1␣ after VD (52), indicative of more significant hypoxia in this organ than other pelvic organs. Therefore, the edema could have occurred as a consequence of tissue inflammation secondary to hypoxia (54).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous work showing marked edema after 4 h of VD associated with thinning of the UVS and interstitial swelling between striated muscle fibers (28). In addition, we previously showed that the urethra is the only organ demon- strating a significant increase in hypoxia-inducible factor-1␣ after VD (52), indicative of more significant hypoxia in this organ than other pelvic organs. Therefore, the edema could have occurred as a consequence of tissue inflammation secondary to hypoxia (54).…”
Section: Discussionsupporting
confidence: 93%
“…The most commonly utilized model consists of VD with a Foley catheter balloon (8,28). Longer-duration distension has been shown to have more severe outcomes with a longer recovery time (37,52). In addition, hypoxia and reperfusion have been shown to be likely mechanisms for the injury to continence structures during VD (12,46,54).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of differences in rectal MCP-3 expression after VD injury in our study is consistent with the findings of Woo et al, 22,23 but is in contrast to the findings of Wood et al 13 who observed a 21-fold increase in relative MCP-3 expression in the rectum immediately after VD injury. It should be noted, however, that in the Wood study this difference was only seen after 4 hours of sustained VD injury, as there was no relative difference in MCP-3 expression after 1 hour of VD as compared to controls.…”
Section: Commentsupporting
confidence: 91%
“…13 MCP-3 is a mesenchymal stem cell (MSC) homing cytokine, which plays a key role in post-ischemia recovery. 14 Moreover, we have demonstrated selective homing of intravenously infused MSCs to the urethra, following VD.…”
Section: Introductionmentioning
confidence: 99%
“…These time points were selected based on the timecourse of cytokine expression in previous studies. 7,9,22,25,26 Loxl1 KO mouse gestation duration is approximately 21 days, so, as a feasible time point for studying the effects of pregnancy in the absence of delivery as a control for delivered mice, tissues were harvested on the 20 th day of gestation, prior to parturition for the pregnant group (Figure 1A). Sixty-four additional age-matched virgin Loxl1 KO female mice were utilized as sham cesarean injury controls or unmanipulated virgin controls (Figure 1A).…”
Section: Methodsmentioning
confidence: 99%